Studies on gonococcus infection. XII. Colony color and opacity varienats of gonococci. - Swanson, J (1978)
Colonies with markedly differing color and opacity characteristics were found for Neisseria gonorrhoeae propagated on translucent, solid medium. These optical properties of gonococcal colonies were independent of pilation and appeared to be related to the degree of aggregation among the gonococci comprising the colonies. Dark, opaque colonies contained highly aggregated gonococci which were more susceptible to killing and to solubilization of their 125-labeled surface components than were organisms comprising light, transparent colony forms.